Size and sex composition of population in India 1901-1961. - Desai, P.B. (Bombay, 1969)
This work the first in series of studies which the Demographic Research Centre of the Institute of Economic Growth has undertaken on the census data. deals with the two basic demographic variables, namely, the size and the sex ratio the population. It is detailed examination of the census data for the period 1901 1961. An analysis of the data from seven censuses during this period has been made for the national population as well as different segments, viz. census zones, states, rural and urban segments, different size classes of towns and cities individually. Detailed examination also undertaken for ascertaining relationship of size and sex composition with other important demographic variables like age structure, migration, working force, and the geographical distribution of the population, with particular reference to cities. The Appendix the volume gives series analytical tables containing data of the seven censuses for both the variables under reference. The monograph helps identify particular segments population that have grown rapidly in the course of the period and the segments of population for which the incidence of sex dis proportion in the population particularly acute.
Keywords: Demography